Comparison of calcium absorption from nano- and micro-sized calcium salts using everted gut sac technique - RANJAN, RAKESH; SAWAL, R K; RANJAN, AMITA; PATIL, N V (The Indian Journal of Animal Sciences, 2019)
The present study aimed to compare the calcium absorption from calcium carbonate and calcium phosphate in nano and micro-sized forms using everted gut sac technique. It was found that calcium concentrations in sac fluid were higher after incubation in nano-sized calcium carbonate than micro-sized calcium carbonate by 18.23% at 45 min and 21.39% at 75 min. Likewise, Ca concentration in sac fluid was 20.50 and 15.13% higher in nano-sized calcium phosphate than those incubated in micro-sized forms at 45 and 75 min, respectively. Present study revealed that calcium carbonate and calcium phosphate are more extensively absorbed in nano-sized forms than in microsized forms, suggesting their possible use as calcium supplements in poultry and livestock farming.